Morocco : Ex-Post Evaluation of Exceptional Access Under the 2014 Precautionary and Liquidity Line Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Morocco's Ex Post Evaluation of Exceptional Access Under the 2014 Precautionary and Liquidity Line (PLL) Arrangement. The case of Morocco demonstrated that with strong ownership, parsimonious conditionality can be effective in delivering on program commitments. The PLL arrangement with Morocco was successful in helping to reduce vulnerabilities. Fiscal balances improved, and the fiscal objective-a gradual reduction of the budget deficit to 3 percent of GDP by 2017-appropriately balanced the need to bring the debt-to-GDP ratio down closer to 60 percent in the medium term, while allowing for necessary investment and social spending. Going forward, to achieve higher and more inclusive growth, Morocco will require continued strong policies and accelerated fiscal and structural reforms.